Equity Research - Verizon Inc - Serrumbia, Mariana Vilhena Gomes (2020)
The Master Dissertation is an Equity Research on Verizon Inc. The purpose is to elaborate a detailed analysis ofthe company andto estimate,asof31st December 2020theexpected share price. In this research it can be found an analysis ofthe trends and the competitive position of Verizonin its industry as well as the rationale behind the forecasted values and the value drivers.